Cork processing with supercritical carbon dioxide: impregnation and sorption studies - Aroso, Ivo Manuel Ascensão (2015)
The present study relates to the use of supercritical carbon dioxide (SCCO2) to modify the properties of cork by incorporation of new molecules. The impact of SCCO2processing on the morphology and on the mechanical properties was found to be negligible.The impregnation of disperse blue 14 (blue dye) on cubic shaped cork samples of 5mm occurs progressively,is dependent of the processing conditions and of the presence of lenticels and growth rings. The impregnation of the samples bulk was achieved with processing at 10MPa and 313K for 16 h. The solubility and sorption of SCCO2 in the cork matrix was measured using circular discs and the diffusion coefficients calculated to be on the order of 10â 8 cm2/s, the same order as for wood materials. This work demonstrates the feasibility of supercritical fluid technology to impart new features to cork, which may lead to innovative architectural, outdoor and industrial applications.